The Role of Religious Culture in Forming the Character of Vocational High School Students - Sudirman Sudirman; Muhammad Alda Wijayanto; Endang Fatmawati; Revi Sesario; Siti Aisyah Hanim (Edunesia: Jurnal Ilmiah Pendidikan, 2023)
This study aims to determine the Religious Culture at SMK Islamic Center Baiturrahman Semarang, what culture is applied, and the Management of Character Education through Religious Culture at SMK Islamic Center Baiturrahman Semarang. This study uses a qualitative description method. Data collection was conducted by researchers using observation, interviews, and documentation. Then to check the validity of the data, it is done through data triangulation techniques and data analysis. The results of this study: (1) Religious culture at the Islamic Center Baiturrahman Vocational School Semarang was created in various forms of religious habituation that are applied in schools; (2) The application of religious culture through 3 ways, namely the integration of character education through teaching and learning activities, through extracurricular activities, and through habituation in schools. (3) Planning for character education through religious culture at SMK Islamic Center Baiturrahman Semarang has long-term priorities and short-term priorities